Overall survival in lower IPSS risk MDS by receipt of iron chelation therapy, adjusting for patient‐related factors and measuring from time of first red blood cell transfusion dependence: an MDS‐CAN analysis. (5th July 2017) - Leitch, Heather A.; Parmar, Ambica; Wells, Richard A.; Chodirker, Lisa; Zhu, Nancy; Nevill, Thomas J.; Yee, Karen W. L.; Leber, Brian; Keating, Mary‐Margaret; Sabloff, Mitchell; St. Hilaire, Eve; Kumar, Rajat; et al.
Summary: Analyses suggest iron overload in red blood cell (RBC) transfusion‐dependent (TD) patients with myleodysplastic syndrome (MDS) portends inferior overall survival (OS) that is attenuated by iron chelation therapy (ICT) but may be biassed by unbalanced patient‐related factors. The Canadian MDS Registry prospectively measures frailty, comorbidity and disability. We analysed OS by receipt of ICT, adjusting for these patient‐related factors. TD International Prognostic Scoring System (IPSS) low and intermediate‐1 risk MDS, at RBC TD, were included. Predictive factors for OS were determined. A matched pair analysis considering age, revised IPSS, TD severity, time from MDS diagnosis to TD, and receipt of disease‐modifying agents was conducted. Of 239 patients, 83 received ICT; frailty, comorbidity and disability did not differ from non‐ICT patients. Median OS from TD was superior in ICT patients (5·2 vs. 2·1 years; P < 0·0001). By multivariate analysis, not receiving ICT independently predicted inferior OS, (hazard ratio for death 2·0, P = 0·03). In matched pair analysis, OS remained superior for ICT patients ( P = 0·02). In this prospective, non‐randomized analysis, receiving ICT was associated with superior OS in lower IPSS risk MDS, adjusting for age, frailty, comorbidity, disability, revised IPSS, TD severity, time to TD and receiving disease‐modifying agents. This provides additional evidence that ICT may confer clinical benefit.